2014
DOI: 10.1590/s1677-5538.ibju.2014.02.17
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of the deposit of collagen in bladder suture of rats treated with tacrolimus combined with mycophenolate-mofetil

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: To evaluate the synthesis of type I (mature) and type III (immature) collagen in bladder suture of rats treated with a combination of tacrolimus and mycophenolate mofetil for 15 days. Materials and Methods:Thirty rats were divided into 3 groups: the sham, control and experimental groups. All the animals underwent laparotomy, cystotomy and bladder suture in two planes with surgical PDS 5-0 thread. The sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Willem et al showed in the rodent model that MMF may negatively affect the abdominal wall wound healing but had no effect on colonic anastomosis [43]. e bladder wound of rats treated with tacrolimus (TAC) and MMF has more immature collagen (type III) as compared to the control group, which has mature collagen (type I) [44]. MMF may cause inhibition of fibroblast by depletion of guanosine.…”
Section: Is It Mtor-i Only?mentioning
confidence: 99%
“…Willem et al showed in the rodent model that MMF may negatively affect the abdominal wall wound healing but had no effect on colonic anastomosis [43]. e bladder wound of rats treated with tacrolimus (TAC) and MMF has more immature collagen (type III) as compared to the control group, which has mature collagen (type I) [44]. MMF may cause inhibition of fibroblast by depletion of guanosine.…”
Section: Is It Mtor-i Only?mentioning
confidence: 99%